Social Work and Science. - Gehlert, Sarah (Research on Social Work Practice, 2016)
Interest has grown in the past few years about the place of social work in science. Questions remain, such as whether social work should be considered a science, and if so, where it fits into the constellation of sciences. This article attempts to shed light on these questions. After briefly considering past and present constructions of science and reflecting on views of science within the social work profession over time, we present an argument for how social work contributes to predominant questions facing science today through its unique ability to draw together and integrate knowledge from a variety of disciplines. Finally, we address how the profession can best prepare the coming generation of social workers to operate to their full potential in the current transdisciplinary world of science.